PENGARUH KOMPETENSI DAN KINERJA GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MASA PANDEMI DI SD NEGERI 001 SEKUPANG KOTA BATAM - Daeli, Betesa; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2022)
This review plans to choose the effect of instructor ability and execution at the same time and somewhat on understudy learning inspiration at SD Negeri 001 Sekupang Batam City. The strategy for gathering information is through a poll overview with an example of 114 respondents. The insightful strategy utilized is numerous relapse examination and the sort of exploration utilized in this review is the study technique. The outcomes acquired on the ability variable on understudies' learning inspiration, the t esteem is 2.640 > t table 1.658, and Sig 0.001 <0.05, so it tends to be inferred that the capability variable affects understudies' learning inspiration. The educator execution variable on understudy learning inspiration has a t worth of 1.918 > t table 1.658, and Sig 0.003 <0.05, so it tends to be presumed that the instructor execution variable affects understudy learning inspiration. In the mean time, all the while, the determined f esteem is 62,021 > f table 3.08 and Sig 0.000 <0.05. Hence, it might be construed that Ho is excused and Ha is recognized or as such, the ability and instructor execution factors at the same time impact understudies' learning inspiration with a R square worth of 0.679, implying that it shows that the skill and educator execution factors can clarify the factors of understudy learning inspiration. of 67.9%, while 32.1% is clarified by different factors not analyzed in this review. Keywords: competence, teacher performancee and student learning motivation